The sexist beliefs that underlie in the pedagogy about obesity in physical education classes - Núñez Rivas, Hilda Patricia (2019)
The physical education class and the teachers guide to this subject are key elements to make physical activity a habit for life. This article describes the sexist beliefs that underlie in the pedagogy about obesity in physical education classes. The ethnographic method was used in a public urban school of San José, Costa Rica. A sample of 210 students and five physical education teachers participated. The results indicate that sexist beliefs of teachers affect the pedagogical treatment of obesity. Among these effects are the exclusion and inattention of students with obesity in the practice of this subject and the privilege that teachers give to students with normal nutritional status. The data show that girls and boys with obesity or those who lack traits related to masculinity fail in physical activity and are excluded. It is necessary to re-signify the practice of the teacher of physical education to achieve an inclusive education.